Taking Action or Thinking About It? State Orientation and Rumination Are Correlated in Athletes - Kröhler, Alena; Berti, Stefan (Frontiers in Psychology, 2019)
Athletic performance in competitive sports relies heavily on the ability to cope effectively with stressful situations. In contrast, some athletes report that their thoughts revolve around the future or past and not around the actual demands during competitions. In those specific stressful situations, the lack of focus like an unintended fixation on repetitive cognitions can have fatal consequences with regard to the performance. Especially when competitors are close in their athletic capabilities, differences in effectively coping with stress and mental stability may decide about winning and losing. One established factor of performing effectively under pressure is the individual tendency to either focus on taking action (i.e., action orientation) or on focusing on the own emotions (i.e., state orientation). It is widely acknowledged that state-oriented athletes have disadvantages in performing under stress. Moreover, the action control theory (Kuhl, 1983; 1994a) claims that state orientation is related to ruminative cognitions, which itself is assumed to impair performance on the long-term. We tested this hypothesis in 157 competitive athletes from different sports (including individual and team sports). Regression analysis demonstrate a substantial correlation of failure-related action orientation (i.e., state orientation) with different measures of rumination (including general, clinically relevant, and competition related rumination). In addition, general (i.e., content independent) rumination also correlated substantially with a rumination scale adapted specifically to sports-related competition. These results suggest (1) that a sports and competition related ruminative mechanism exist and (2) that ruminative cognitions are related to the cognitive basis of state orientation. While our study does not allow for a causal interpretation, it provides an additional approach to investigate mental factors underlying inter-individual differences in athletic performance under stress and pressure.